How designers think : the design process demystified. - Lawson, Bryan, ....- (Amsterdam : Elsevier, 2006)
Part 1: What is Design: Introduction The changing role of the designer Route maps of the design process Part 2: Problems and Solutions: The components of design problems Meaurement, criteria and judgement in decision A model of design problems Problems, solutions and the design process Part 3: Design Thinking: Types and styles of thinking Creative thinking Design as Conversation Guiding principles Design strategies Design tactics Design traps Designing with drawings Designing with others Design with computers Quo vadis? Case Studies: Gordon Murray, James Dyson, Edward Cullinan, Glenn Murcutt.
Keywords: Architectonisch ontwerpen; Industriële vormgeving